Simulator Rangkaian Mikrokontroler Arduino Uno sebagai Media Pembelajaran menggunakan Proteus - Amri Rahman; Taali Taali (Jurnal Pendidikan Teknik Elektro, 2023)
Technological developments cannot be denied because they have changed the pattern of the teaching system, so that every educator and student must take advantage of technological developments as a means of delivering education. Many methods and strategies that must be applied in making it happen. Industrial Electrical Engineering Study Program, Department of Electrical Engineering, Faculty of Engineering, Padang State University is one of the majors whose learning process is practicum in nature. So we need a solution to address the needs of students in gaining knowledge and expertise in practicum through research entitled Arduino UNO Microcontroller Circuit Simulator as Learning Media Using Proteus. By utilizing technological developments, it can produce learning media in the form of a simulator of the Arduino UNO microcontroller circuit using Proteus software as a valid and practical medium. The completion of this research uses the R&D research method with 4-D Development namely Define, Design, Develop, Dessiminate. By examining the two main things that exist in a jobsheet, namely the validity and practicality of which the data is processed with the statistical formula Aiken's V. The research results obtained in testing the validity of the material and media as a whole can be concluded that the interface engineering practicum jobsheet is declared valid for use in the learning process. The results of the practicality test by the lecturers who supervised the course and also tested it on 22 students were stated to be very practical. The findings of the study with positive results show that the interface engineering practicum jobsheet is a useful tool for student education.